Radiation exposure and safety in low-dose CT-guided glycerol rhizotomy for trigeminal Neuralgia outside the operating room - Dostal, Jiri; Baxa, Jan; Stepankova, Jana; Seidl, Miroslav; Mracek, Jan; Lavicka, Pavel; Malkus, Tomas; Priban, Vladimir (Acta neurochirurgica, 2024)
BACKGROUND: Percutaneous rhizotomy of the Gasserian ganglion is a well-established intervention for patients suffering from refractory trigeminal pain, not amenable to pharmacological management or microvascular decompression. Traditionally conducted under fluoroscopic guidance using Hartel's technique, this study investigates a modified approach employing low-dose CT guidance to achieve maximal procedural precision and safety with the emphasis on minimizing radiation exposure. METHODS: A retrospective analysis of patients undergoing percutaneous rhizotomy of the Gasserian ganglion at our institution was undertaken. Procedures were divided into fluoroscopy and CT-guided foramen ovale (FO) cannulation cohorts. Radiation doses were assessed, excluding cases with incomplete data. The study included 32 procedures in the fluoroscopy group and 30 in the CT group. RESULTS: In the CT-guided group, the median effective dose was 0.21 mSv. The median number of CT scans per procedure was 4.5, and the median procedure time was 15 min. Successful FO cannulation was achieved in all 30 procedures (100%). In the fluoroscopy group, the median effective dose was 0.022 mSv, and the median procedure time was 15 min. Cannulation of FO was successful in 31 of 32 procedures (96.9%). The only complications in the CT-guided group were three minor cheek hematomas. Immediate pain relief in the CT-guided group was reported in 25 of 30 procedures (83.3%), 22 of 30 (73.3%) provided relief at one month, and 10 of 18 (55.6%) procedures resulting in pain relief at one month continued to provide relief after two years. CONCLUSION: Low-dose CT-guided percutaneous rhizotomy conducted in the radiology suite carries negligible radiation exposure for patients and eliminates it for personnel. This method is fast, simple, precise, and carries a very low risk of complications.
Keywords: senioři; neuralgie trigeminu; dávka záření; Rhizotomy; Fluoroscopy; radiační expozice; Trigeminal Neuralgia; Retrospective Studies; Tomography, X-Ray Computed; výsledek terapie; Middle Aged; mužské pohlaví; Adult; ganglion trigeminale; fluoroskopie; Radiation Exposure; Trigeminal Ganglion; ženské pohlaví; rizotomie; retrospektivní studie; Humans; Radiation Dosage; lidé středního věku; dospělí; počítačová rentgenová tomografie; Female; Aged; Treatment Outcome; lidé; Male